2006
DOI: 10.1002/art.22193
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of tumor necrosis factor inhibitors in rheumatoid arthritis in an observational cohort study: Comparison of patients according to their eligibility for major randomized clinical trials

Abstract: Objective. Randomized clinical trials (RCTs) evaluate the efficacy of treatments in selected groups of patients defined by strict inclusion criteria. The value of these trials in predicting therapeutic effectiveness in "real world" patients is limited. This observational cohort study was designed to complement the knowledge obtained in RCTs by evaluating the effectiveness of tumor necrosis factor (TNF) inhibitors in patients with rheumatoid arthritis (RA) according to their eligibility for the major trials.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(128 citation statements)
references
References 25 publications
7
106
0
15
Order By: Relevance
“…In clinical practice, many patients initiating RTX have lower disease activity levels compared with those enrolled in anti-TNF RCT, a factor that further influences evaluations of effectiveness 12,13,14 . Most observational data examining the effectiveness of RTX in routine clinical practice have been reported from European registries 15,16,17,18,19,20,21,22 , with scant information currently available from the United States 23 .…”
Section: Rheumatologymentioning
confidence: 99%
“…In clinical practice, many patients initiating RTX have lower disease activity levels compared with those enrolled in anti-TNF RCT, a factor that further influences evaluations of effectiveness 12,13,14 . Most observational data examining the effectiveness of RTX in routine clinical practice have been reported from European registries 15,16,17,18,19,20,21,22 , with scant information currently available from the United States 23 .…”
Section: Rheumatologymentioning
confidence: 99%
“…However, they restrict patient inclusion, usually in an attempt to recruit a homogenous group of patients and thus are not always representative of the cohort of patients who will eventually go on to receive biologic therapies. 4,5 They are usually not powered to study the risk of less common outcomes, such as serious infection. As recruitment and follow-up are usually over a short period of time, latent effects, such as the risk of malignancy, may not be observed.…”
Section: What Can We Learn About Biologic Therapies Using Biologics Rmentioning
confidence: 99%
“…4,5 This was explained by both a proportion of patients who were too ill or disabled to participate, but there was also a proportion of patients whose disease was not active enough to be eligible. More recent data from the British register have shown that patients who start rituximab or tocilizumab as a first line biologic, as opposed to a TNFI, have higher frequencies of important comorbidities such as prior cancer or interstitial lung disease, conditions which often preclude participation in RCTs.…”
Section: The Use Of Biologics In Clinical Practicementioning
confidence: 99%
“…Randomized clinical trials (RCTs) are widely accepted as the gold standard to evaluate the effectiveness of treatment (1). This design ensures the internal validity of results, i.e., the results cannot be explained by confounding (2).…”
Section: Introductionmentioning
confidence: 99%
“…However, observational studies are often viewed as less (internally) valid because of confounding, especially confounding by indication. It has also been shown that well-designed observational studies might not systematically over-or underestimate the magnitude of the effects of treatment as compared to RCTs (1)(2)(3)(4)(5)(6)(7). Hence, we are still in need of a methodology for estimating the treatment effect that fits both the need for internal validity and for generalizability (also sometimes referred to as external validity).…”
Section: Introductionmentioning
confidence: 99%